Unraveling the Charge Storage and Activity‐Enhancing Mechanisms of Zn‐Doping Perovskite Fluorides and Engineering the Electrodes and Electrolytes for Wide‐Temperature Aqueous Supercabatteries. (14th October 2021) - Jia, Ziyang; Ding, Rui; Yu, Wujiang; Li, Yi; Wang, Ailin; Liu, Miao; Yang, Feng; Sun, Xiujuan; Liu, Enhui
Abstract: Herein, a trimetallic Ni–Co–Zn perovskite fluoride (ABF3 ) (denoted as KNCZF) electrode material is explored for advanced aqueous supercabatteries (ASCBs), with KNCZF and activated carbon–FeBiCu@reduced graphene oxides (AC–FeBiCu@rGO) as cathode and anode, respectively, which outperform aqueous supercapacitors (ASCs) and batteries (ABs) with AC and FeBiCu@rGO anodes because of the synergistic effect of pseudocapacitive (KNCZF), capacitive (AC), and faradaic (FeBiCu@rGO) responses. One of the important findings is that the KNCZF shows a typical bulk phase conversion mechanism for charge storage in the alkaline media with the transition of ABF3 perovskite nanocrystals into amorphous metal oxides/(oxy)hydroxides nanosheets, showing the redox‐active and redox‐inert roles for the Ni/Co and Zn species, respectively, which can be deduced by various ex‐situ techniques. Another interesting finding is that the redox‐inert Zn species largely enhance the activity of Ni/Co redox‐active species in the ABF3 materials, mainly owing to the promotion of surface electroactive sites, adsorption of OH −, and charge transfer of surface Ni/Co atoms by Zn‐doping, which can be proved by ex‐situ characterizations and theoretical calculations. Overall, this study reveals the structure–activity relationship and charge storage mechanisms of Zn‐doping ABF3 materials for advanced ASCBs, showing a great impact on developing advanced electrochemical energy storage. Abstract : A Zn‐doping perovskite fluoride (ABF3 ) (K–Ni–Co–Zn–F) is explored for aqueous (alkaline) supercabatteries (ASCBs), showing a typical bulk phase conversion mechanism for charge storage with the transition of ABF3 perovskite nanocrystals into amorphous metal oxides/(oxy)hydroxides nanosheets. Redox‐inert Zn largely enhances the activity of redox‐active Ni/Co owing to the promotion of electroactive sites, OH − adsorption, and charge transfer of surface Ni/Co atoms.